Efektivitas Manajemen Kepemimpinan dalam Gereja - Johanes Augustinus; Beni Chandra Purba; Budi Kelana (PT. Penerbit Tiga Mutiara, 2023)
Abstract This research discusses the effectiveness of leadership management in the context of a church. The church, as a Christian community, possesses distinct characteristics, including the diverse backgrounds of its members in terms of age, occupation, education, and social status. Unlike other organizations with financial orientations, the church aims to fulfill the spiritual needs of its members, emphasizing a focus on conformity to Christ. Church leaders are expected not only to exercise authority for regulation but also to empower the congregation. Effective church leadership involves empowerment, exploration of potentials, and acceptance of differences. Church leaders play a crucial role in the effective growth of the church, and leadership management is key to achieving the church's vision and mission. The research methodology employed is a qualitative descriptive approach with literature review. In-depth analysis of the concept of leadership management in the church is conducted by connecting information from various sources, including books, journals, articles, and relevant websites. The findings indicate that the understanding of the church involves spiritual and organizational dimensions, necessitating effective leadership management. Leadership centered on biblical values, resource management, and the empowerment of congregation members becomes crucial in attaining church goals. The differences and uniqueness of the church demand leaders to implement suitable leadership styles, such as democracy, to support the potential of each member. From this research, it can be observed that effective leadership management in the church plays a crucial role in achieving spiritual and organizational objectives. Church leaders need to develop strategies in line with the church's characteristics and leverage the potential of congregation members for sustainable growth.